Validation of the Patient Activation Measure in kidney stone disease patients - Murad, Liam; Abou Samra, Sophie; Schwartz, Ryan; Assad, Anis; Penniston, Kristina; Bensaadi, Kahina; Meskawi, Malek; Bhojani, Naeem (Canadian Urological Association Journal, 2024)
INTRODUCTION: We aimed to validate the Patient Activation Measure (PAM) within a kidney stone disease (KSD ) population, determine the variability of patient activation within this population, and characterize relationships between activation and variables such as health literacy, quality of life, and demographics. METHODS: This cross-sectional study includes individuals 18 years or older followed for KSD at University of Montreal Hospital Center. Demographic data and responses for the PAM, Wisconsin Stone Quality of Life scale, and Health Literacy Questionnaire (HL Q) were acquired. RESULTS: Females and those with poor medication adherence were found to have significantly lower activation. The HL Q dimensions “Actively managing my health,” “Navigating the healthcare system,” and “Understand health information well enough to know what to do” were associated with significantly higher activation. Rasch analysis revealed an item reliability of 0.81, a person reliability of 0.98, and a Cronbach’s alpha of 0.88. Regarding item fit, only item 1 (When all is said and done, I am the person who is responsible for taking care of my health) fit poorly with the model. Principle component analysis revealed evidence of a second dimension, accounting for 9.0% of the variation in observed responses. CONCLUSIONS: Female sex and poor medication adherence were associated with significantly lower activation. Aspects of health literacy concurring with the precise definition of “activation” were associated with significantly higher PAM scores. The PAM was found to have good person and item reliability, and good internal consistency; however, principal component analysis revealed that construct validity is possibly threatened by multidimensionality.